2022
DOI: 10.18240/ijo.2022.12.13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical feature and predictive factor analysis for spontaneous regression of retinopathy of prematurity in a Chinese population

Abstract: AIM: To investigate the ratio of spontaneous regression of retinopathy of prematurity (ROP) and to explore the possible relevant predictive factors. METHODS: A retrospective review of 405 infants who were diagnosed with ROP and mother during pregnancy were collected. Stage, zone, and duration of ROP were recorded. Statistical analysis was performed on 51 possible predictive factors. RESULTS: Totally 356 infants showed spontaneous regression. The incidence was 100%, 95.3%, and 22.7% in stage 1, 2, and 3, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…With the development of assisted reproductive technology, the incidence of multiple births has further increased, so the impact of multiple births on ROP deserves our attention. Numerous studies have identified long-term mechanical ventilation as a risk factor for ROP and severe ROP [18][19][20] . In this study, non-invasive ventilation was associated with severe ROP (P<0.05) and was a protective factor.…”
Section: Retinopathy Of Prematurity In Chinamentioning
confidence: 99%
“…With the development of assisted reproductive technology, the incidence of multiple births has further increased, so the impact of multiple births on ROP deserves our attention. Numerous studies have identified long-term mechanical ventilation as a risk factor for ROP and severe ROP [18][19][20] . In this study, non-invasive ventilation was associated with severe ROP (P<0.05) and was a protective factor.…”
Section: Retinopathy Of Prematurity In Chinamentioning
confidence: 99%